Case Study of Implementation of Adverse Event Prevention Program: Decubitus Ulcer in Bedrest Patient with Stroke in the ICU Room with S.S.K.I.N Approach - Rizky Lukman Saputra; Anisah Ardiana; Kholid Rosyidi M.N; Yudho Tri Handoko (Caring : Jurnal Keperawatan, 2024)
Patient safety is one of the aspects of providing excellent service for patients in hospitals, especially in the ICU. One method of managing patient safety is to prevent pressure ulcers in the ICU. The aim of this study is to explain the management of pressure ulcer prevention in the ICU for bedridden stroke patients using an intervention approach with form chart media. The research method used in this study is a case study design that includes assessment processes, data analysis, diagnostic rehabilitation, intervention, implementation, and evaluation. We collected data through observation, interviews, and physical examinations. We carried out the intervention in two shifts. We measured the risk of pressure ulcers using the Braden scale, provided health education to the family, and ensured the nurse correctly filled out the form. The obstacle to increasing the number of nurses is the workload and the feeling that human resources are still insufficient. There are no signs of pressure sores on the patient's back. In the implementation of the pressure ulcer prevention program using the skin approach, family involvement is necessary to ensure the program continues without adding to the workload of nurses in the ICU. Conclusion: Modifications to the formchart and family involvement in the program are necessary for the implementation of the pressure ulcer prevention program using formchart media in the ICU.